Heavy Metals in Water, Soils and Sediments of La Villa River Basin- Panama - José Villarreal Núñez; Adolfo Santo Pineda; Jhon Villalaz Pérez; ván Ramos Zachrisson (International Journal of Plant & Soil Science, 2021)
Determine the concentration of heavy metals in water, sediments, and crops within the La Villa river basin, Herrera and Los Santos provinces, republic of Panama. La Villa river Basin, south central of Panama, in the rainy season of 2016 (May to November) and in the dry season of 2017 (December to April). Twenty two sediments and water samples were taken using the systematic method which consists of selecting sampling points at uniform distances and crops in upper, middle and lower basin. The selected sampling was confined to a preferably rectangular area of 10.0 m x 30.0 m, on which the sub-samples were taken with a number of 15 on each grid, at 0.20m depth. For collecting the water samples, a rod with a clean plastic bottle was introduced against the current of the river. The digestion of sediments and crops to determine the concentration of heavy metals (As, Pb, Cr, Ni, Cu, Mn, Zn and Cd) was carried out according to USEPA (25) method (3051A) (SW-846). In the sediments, in the rainy season, Cu (upper and lower basin) and Mn (all levels) values were found above the USEPA Standards. In the dry season, high values of Mn were found in the middle and lower basin, Cr in the upper and lower basin and As in all areas of the basin. In the rainy and dry seasons, high levels of Mn, Zn, Cr, Cd and Pb were found in the waters of the rivers that make up the basin. The main crops at each height of the basin were analyzed, determining high levels of As and Cr in the upper basin, in the middle and lower basin Cr and Cd. It is necessary to monitor the concentration of heavy metals in sediments of La Villa river basin because 90% of the agrochemicals that enter the country is destined for agriculture. Each Panamanian consumes (does not ingest) 3 kg of agrochemicals annually, exceeding six times the amount used in Central America. Due to their geological origin, these soils are rich in copper, manganese and arsenic, latter being associated with iron oxides and sulfides but there is also great influence of anthropogenic activities, agriculture and industries. Some metals such as lead and arsenic showed low solubility in water but showed high concentration in sediments. Chromium and cadmium present in crops come from water.
Estudio de la Cuenca del Río La Villa
Keywords: cadmium; arsenic; chromium; lead; trace elements